In Vivo PET Imaging of Adenosine 2A Receptors in Neuroinflammatory and Neurodegenerative Disease - Anna Vuorimaa; Eero Rissanen; Laura Airas (Hindawi Limited, 2022)
Adenosine receptors are G-protein coupled P1 purinergic receptors that are broadly expressed in the peripheral immune system, vasculature, and the central nervous system (CNS). Within the immune system, adenosine 2A (A2A) receptor-mediated signaling
exerts a suppressive effect on ongoing inflammation. In healthy CNS, A2A receptors are expressed mainly within the neurons of
the basal ganglia. Alterations in A2A receptor function and expression have been noted in movement disorders, and in Parkinson’s
disease pharmacologicalA2A receptor antagonism leads to diminishedmotor symptoms. AlthoughA2A receptors are expressed only at a low level in the healthy CNS outside striatum, pathological challenge or inflammation has been shown to lead to upregulation of A2A receptors in extrastriatal CNS tissue, and this has been successfully quantitated using in vivo positron emission tomography (PET) imaging and A2A receptor-binding radioligands. Several radioligands for PET imaging of A2A receptors have been developed in recent years, and A2A receptor-targeting PET imaging may thus provide a potential additional tool to evaluate various aspects of neuroinflammation in vivo. This review article provides a brief overview of A2A receptors in healthy brain and in a selection of most important neurological diseases and describes the recent advances in A2A receptor-targeting PET imaging studies.